(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2019)
Background: Cardiovascular disease is the leading cause of morbidity and mortality in patients of Chronic Kidney Disease (CKD). According to recent studies, insulin resistance and compensatory hyperinsulinemia may have some important roles in cardio-renovascular complications of these patients. So, the aim of this study was to evaluate the insulin resistance status in nondiabetic CKD patients and whether it correlates with glomerular function. Materials and methods: This crosssectional comparative study was carried out in the Department of Biochemistry, Chattogram Medical College from January to December, 2016. A total of 130 subjects of 30- 60 years were included by nonprobability consecutive sampling. Of them, 80 were nondiabetic CKD patients of stages III-V and 50 were healthy controls. Fasting plasma glucose, creatinine and insulin concentrations were measured using automated analyzers. Insulin resistance index was determined by Homeostatic Model Assessment Insulin Resistance (HOMA-IR) whereas eGFR was calculated by MDRD formula. Results: The nondiabetic CKD patients had significantly higher mean fasting plasma insulin (18.08 mIU/L) compared to controls (9.43 mIU/L). They also showed significantly higher mean HOMA-IR values (4.37) relative to healthy individuals (2.23). Overall, insulin resistance was 66% in nondiabetic CKD patients vs. 18% in controls. There was significant association of insulin resistance with CKD. But, HOMA-IR did not seem to correlate with CKD stages or eGFR. Conclusion: In conclusion, this study revealed significant association between insulin resistance and nondiabetic CKD, even though substantial correlation between insulin resistance and glomerular filtration rate was absent. JCMCTA 2019 ; 30 (1) : 51-55